Unimolecular Micelle-Based Hybrid System for Perivascular Drug Delivery Produces Long-Term Efficacy for Neointima Attenuation in Rats - Chen, Guojun (Biomacromolecules, 2017)
At present, there are no clinical options for preventing neointima-caused (re)stenosis after open surgery such as bypass surgery for treating flow-limiting vascular disease. Perivascular drug delivery is a promising strategy, but in translational research, it remains a major challenge to achieve long-term (e.g., > 3 months) anti(re)stenotic efficacy. In this study, we engineered a unique drug delivery system consisting of durable unimolecular micelles, formed by single multiarm star amphiphilic block copolymers with only covalent bonds, and a thermosensitive hydrogel formed by a poly(lactide-co-glycolide)–poly(ethylene glycol)–poly(lactide-co-glycolide) triblock copolymer (abbreviated as triblock gel) that is stable for about 4 weeks in vitro. The drug-containing unimolecular micelles (UMs) suspended in Triblock gel were able to sustain rapamycin release for over 4 months. Remarkably, even 3 months after perivascular application of the rapamycin-loaded micelles in Triblock gel in the rat model, the intimal/medial area ratio (a restenosis measure) was still 80% inhibited compared to the control treated with empty micelle/gel (no drug). This could not be achieved by applying rapamycin in Triblock gel alone, which reduced the intimal/medial ratio only by 27%. In summary, we created a new UM/Triblock gel hybrid system for perivascular drug delivery, which produced a rare feat of 3-month restenosis inhibition in animal tests. This system exhibits a real potential for further translation into an anti(re)stenotic application with open surgery.